Implementation of Enterprise Resource Planning for the Supply Chain Management of the Food and Beverage Department at Macao Entertainment Corp - Vai, Fong Tou; Lee, Leanda; Negreiros, Joao (Information Resources Management Journal (IRMJ), 2014)
One of the six gaming concession holders in Macao, Macao Entertainment Corp (MEC)1, undertook to centralize three casino/entertainment properties through utilization of a centralized Enterprise Resource Planning (ERP) in April 2010. The Supply Chain (SC) department was the first to apply the ERP in...
Publisher: IGI Global

Personality and learning styles surrounded by W3 software: The Macao Portuguese school case - Negreiros, João; Baptista, Zelia; Lee, Leanda (Education and Information Technologies, 2014)
One of the purposes of this study is to evaluate how the choice of teaching method can be assisted by knowledge of a student’s personality type and learning style. The present research is undertaken in the context of Web 2.0 tools use within the Portuguese literature subject at Escola Portuguesa de Macao (EPM). The Felder-Soloman index of learning style (ILS) and the Myers-Briggs Type Indicator (MBTI) based upon Jung’s theory of psychological nature were used as measures of learning style and personality type with 8th grade EPM students. Descriptive and chi-squared correlation statistical results of the associations between personality and learners types are presented. These results are discussed positing that the knowledge of student’s personality traits and learning styles together may have a notable implication for teaching methods.
Keywords: Escola Portuguesa de Macao (EPM); Felder and Soloman; ILS; MBTI; Myers and Briggs; Web 2.0